The role of neutrophil-lymphocyte ratio in predicting alcohol withdrawal-induced seizures in patients with alcohol use disorder - Ramakan, Enver Denizhan; Büyükakça, Ece; Coşkun, Cemrenaz; Alnıak, İzgi (Journal of Dependence, 2025)
Objective: Alcohol withdrawal seizures are a medical condition, potentially life-threatening, that can occur after the cessation or reduction of alcohol consumption. Inflammatory changes play a major role in alcohol withdrawal symptoms (AWS). The neutrophil-lymphocyte ratio (NLR) is an accessible and straightforward method that can alert clinicians to possible risks in certain clinical conditions and support diagnosis. This study aimed to investigate whether NLR scores would contribute to the prediction of seizure development in patients with AWS. Method: This study was conducted through electronic health records at Bakirkoy Prof. Dr. Mazhar Osman Training and Research Hospital for Psychiatry, Neurology, and Neurosurgery- Specific Care Unit of Research, Treatment and Training Center for Alcohol and Substance Dependence (AMATEM). Thirty patients with alcohol withdrawal seizures (SZ+) and sixty-five alcohol use disorder patients without seizures (SZ-) were enrolled. The participants’ biochemical, sociodemographic and clinical data were collected. Results: The SZ+ group and SZ- group showed similarities in terms of age, mean duration of alcohol use and gender. Neutrophil levels were higher and lymphocyte levels were lower in the SZ+ group compared to the SZ- group. NLR found higher in SZ+ group. This difference between the two groups was significant. Conclusion: NLR is a low-cost, widely available marker that can be used to predict alcohol withdrawal seizures.